Cancer-activated doxorubicin prodrug nanoparticles induce preferential immune response with minimal doxorubicin-related toxicity - Yang, Suah; Shim, Man Kyu; Kim, Woo Jun; Choi, Jiwoong; Nam, Gi-Hoon; Kim, Jeongrae; Kim, Jinseong; Moon, Yujeong; Kim, Han Young; Park, Jooho; Park, Yoon; Kim, In-San; et al. (ELSEVIER SCI LTD, 2021)
The effective chemotherapeutic drug, doxorubicin (DOX), elicits immunogenic cell death (ICD) and additional anticancer immune responses during chemotherapy. However, it also induces severe side effects and systemic immunosuppression, hampering its wide clinical application. Herein, we constructed cancer-activated DOX prodrug by conjugating the cathepsin B-cleavable peptide (Phe-Arg-Arg-Gly, FRRG) to a doxorubicin (DOX), resulting in FRRG-DOX that self-assembled into cancer-activated DOX prodrug nanoparticles (CAP-NPs). The resulting CAP-NPs were further stabilized with the FDA-approved compound, Pluronic F68. CAP-NPs formed stable prodrug nanoparticles and they were specifically cleaved to cytotoxic DOX molecules only in cathepsin Boverexpressing cancer cells, inducing a cancer cell-specific cytotoxicity. In particular, the CAP-NPs induced ICD through cathepsin B-cleavage mechanism only in targeted cancer cells in vitro. In colon tumor-bearing mice, selectively accumulated CAP-NPs at tumors enhanced antitumor immunity without DOX-related severe toxicity, inflammatory response and systemic immunosuppression. Moreover, cytotoxicity against immune cells infiltrated into tumor microenvironment was significantly reduced compared to free DOX, leading to increased response to checkpoint inhibitor immunotherapy. The combinatorial treatment of CAP-NPs with anti-PD-L1 exhibited high rate of complete tumor regression (50%) compared to free DOX with anti-PD-L1. Concurrently, DOX-related side effects were greatly reduced during chemoimmunotherapy. Collectively, our results suggest that cancer-activated DOX prodrug nanoparticles provide a promising approach to increase clinical benefit by inducing an immune response preferentially only to targeted cancer cells, not to normal cells and immune cells, and potentiates checkpoint inhibitor immunotherapy.
Keywords: CATHEPSIN-B; CHEMOTHERAPY; CELLS; DELIVERY; TLR4